2023
DOI: 10.1111/bjh.19046
|View full text |Cite
|
Sign up to set email alerts
|

Double filtration plasmapheresis combined with rituximab for donor‐specific antibody desensitization in haploidentical haematopoietic stem cell transplantation

Lizhen Liu,
Xinyu Ji,
Panpan Zhu
et al.

Abstract: SummaryDonor‐specific anti‐HLA antibodies (DSA) are a major cause of engraftment failure in patients receiving haploidentical haematopoietic stem cell transplantation (Haplo‐HSCT). Double filtration plasmapheresis (DFPP) avoids the unnecessary loss of plasma proteins and increases the efficiency of purification. To investigate the effectiveness of the desensitization protocol including DFPP and rituximab, we conducted a nested case–control study. Thirty‐three patients who had positive DSA were desensitized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In their papers, the authors 7 reported their clinical trial results of investigating the effectiveness of the desensitization protocol including DFPP and rituximab. A total of 132 patients undergoing HHCT were enrolled in the nested case–control retrospective study, including 33 with DSAs and 99 without DSAs.…”
Section: Methods Mechanisms Resultsmentioning
confidence: 99%
“…In their papers, the authors 7 reported their clinical trial results of investigating the effectiveness of the desensitization protocol including DFPP and rituximab. A total of 132 patients undergoing HHCT were enrolled in the nested case–control retrospective study, including 33 with DSAs and 99 without DSAs.…”
Section: Methods Mechanisms Resultsmentioning
confidence: 99%